Uniform Nanosecond Pulsed Dielectric Barrier Discharge Plasma Enhances Anti‐Tumor Effects by Induction of Immunogenic Cell Death in Tumors and Stimulation of Macrophages. Issue 12 (7th October 2015) - Lin, Abraham; Truong, Billy; Pappas, Arthur; Kirifides, Lawrence; Oubarri, Ahmed; Chen, Shuyang; Lin, Shaojun; Dobrynin, Danil; Fridman, Gregory; Fridman, Alexander; Sang, Nianli; Miller, Vandana
Abstract : Several have shown plasma to be efficacious against cancer cells in vitro and in vivo with minimal damage to non‐cancerous cells and tissue. Most are focused on direct influence of plasma on tumor cells. However, the body's immune system also plays a crucial role in the control of cancer. A new concept of immunogenic cell death (ICD) has been emerging, where through this modality of cell death, an immune response may be stimulated. The goal of the presented study was to explore a regime of plasma treatment that induces ICD in tumor cells and stimulates anti‐tumor effects in macrophages‐ a key immune cell type involved in the initiation of immunological responses. Here, we show that treatment with uniform nanosecond pulsed dielectric barrier discharge (nspDBD) plasma directly activated anti‐tumor effects in macrophages. We further show macrophage activation following the expression of plasma‐induced damage‐associated molecular patterns (DAMPs) in tumor cells, characteristic of ICD. Abstract : Uniform nanosecond pulsed dielectric barrier discharge plasma enhances anti‐tumor effects of macrophages through 1) induction of immunogenic tumor cell death (ICD) and 2) direct plasma stimulation of macrophages. Plasma induced ICD is determined by measuring two markers of damage associated molecular patterns: extracellular adenosine triphosphate and surface calreticulin. Following co‐culture for 48 hours, tumor cell viability is used as an indicator of enhanced anti‐tumor activity of macrophages.